Stability of phenotypes defined by physiological variables and biomarkers in adults with asthma. Issue 9 (8th July 2014) - Kupczyk, M.; Dahlén, B.; Sterk, P. J.; Nizankowska‐Mogilnicka, E.; Papi, A.; Bel, E. H.; Chanez, P.; Howarth, P. H.; Holgate, S. T.; Brusselle, G.; Siafakas, N. M.; Gjomarkaj, M.; et al.
Abstract Background Although asthma is characterized by variable airways obstruction, most studies of asthma phenotypes are cross‐sectional. The stability of phenotypes defined either by biomarkers or by physiological variables was assessed by repeated measures over 1 year in the Pan‐European BIOAIR cohort of adult asthmatics. Methods A total of 169 patients, 93 with severe asthma (SA) and 76 with mild‐to‐moderate asthma (MA), were examined at six or more visits during 1 year. Asthma phenotype clusters were defined by physiological variables (lung function, reversibility and age of onset of the disease) or by biomarkers (eosinophils and neutrophils in induced sputum). Results After 1 year of follow‐up, the allocation to clusters was changed in 23.6% of all asthma patients when defined by physiological phenotypes and, remarkably, in 42.3% of the patients when stratified according to sputum cellularity (P = 0.034). In the SA cohort, 30% and 48.6% of the patients changed allocation according to physiological and biomarker clustering, respectively. Variability of phenotypes was not influenced by change in oral or inhaled corticosteroid dose, nor by the number of exacerbations. Lower stability of single and repeated measure was found for all evaluated biomarkers (eosinophils, neutrophils and FeNO) in contrast to good stability of physiological variables (FEV1), quality of life and asthma control. Conclusion Phenotypes determined by biomarkers are less stable than those defined by physiological variables, especially in severe asthmatics. The data also imply that definition of asthma phenotypes is improved by repeated measures to account for fluctuations in lung function, biomarkers and asthma control.